Effect of soil depth on the establishment of plants of Rottboellia cochinchinensis (Lour) Clayton in sugar cane (Saccharum officinarum L.). - León, Ramón; Agüero, Renán (Agronomía Mesoamericana, 2006)
Four sugarcane fields with different soil textures (clay loam, sandy loam, clay and loam) were sampled. All fields showed R. cochinchinensis populations with at least 75-150 plants/m2. The number of plants of this weed in 0.25 m2 was determined separately in the microhabitats: rows and between rows. The depth at which each plant emerged was measured. Based on depth emergence, each plant was distributed in one of the next categories: 0, >0-2.5, >2.5-5.0, >5.0-10 and >10.0-15.0 cm. In addition, under greenhouse conditions, seeds were seeded in pots at the maximum depth of each category in order to evaluate the effect of soil depth. Finally, the effect of light and darkness on seed germination were evaluated in Petri dishes under laboratory conditions. In the field evaluations most of the plants emerged from >0-2.5 cm. The second most common category was >2.5-5.0 cm. It seems that those depths provide optimum conditions for germination. There were no differences regarding soil texture or microhabitats. In the greenhouse experiment, the largest germination was observed at 0 cm due to light exposure in this treatment. This was confirmed in the laboratory where light treatment showed also the largest germination. Control strategies that keep the seeds of this species above ground will reduce the number of new seeds in the seed bank and avoid optimum field conditions for its germination. If such strategies include efforts to reduce the seed production of those plants that are able to become established, it could be possible to significantly reduce the seed bank, therefore, it would be easier to control the population of this weed.